Molecular Pathways Linking High-Fat Diet and PM2.5 Exposure to Metabolically Abnormal Obesity: A Systematic Review and Meta-Analysis - Sagrario Lobato; Víctor Manuel Salomón-Soto; Claudia Magaly Espinosa-Méndez; María Nancy Herrera-Moreno; Beatriz García-Solano; Ernestina Pérez-González; Facundo Comba-Marcó-del-Pont; Mireya Montesano-Villamil; Marco Antonio Mora-Ramírez; Claudia Mancilla-Simbro; Ramiro Álvarez-Valenzuela (Biomolecules)
Obesity, influenced by environmental pollutants, can lead to complex metabolic disruptions. This systematic review and meta-analysis examined the molecular mechanisms underlying metabolically abnormal obesity caused by exposure to a high-fat diet (HFD) and fine particulate matter (PM2.5). Following the PRISMA guidelines, articles from 2019 to 2024 were gathered from Scopus, Web of Science, and PubMed, and a random-effects meta-analysis was performed, along with subgroup analyses and pathway enrichment analyses. This study was registered in the Open Science Framework. Thirty-three articles, mainly case–control studies and murine models, were reviewed, and they revealed that combined exposure to HFD and PM2.5 resulted in the greatest weight gain (82.835 g, p = 0.048), alongside increases in high-density lipoproteins, insulin, and the superoxide dismutase. HFD enriched pathways linked to adipocytokine signaling in brown adipose tissue, while PM2.5 impacted genes associated with fat formation. Both exposures downregulated protein metabolism pathways in white adipose tissue and activated stress-response pathways in cardiac tissue. Peroxisome proliferator-activated receptor and AMP-activated protein kinase signaling pathways in the liver were enriched, influencing non-alcoholic fatty liver disease. These findings highlight that combined exposure to HFD and PM2.5 amplifies body weight gain, oxidative stress, and metabolic dysfunction, suggesting a synergistic interaction with significant implications for metabolic health.